2009
DOI: 10.1111/j.1399-5618.2009.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological therapies in bipolar disorder: the effect of illness history on relapse prevention – a systematic review

Abstract: Psychological therapy specifically designed for bipolar disorder is effective in preventing or delaying relapses in bipolar disorders, and there is no clear evidence that the number of previous episodes moderated the effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 24 publications
4
53
2
Order By: Relevance
“…Other studies have found similar results in managing mania symptoms using CBT in comparison with TAU in BD [21]. Patients’ cognitive styles may also be involved in the poor adherence to the psychotherapeutic strategies designed for bipolar patients [35,36]. The prophylaxis of mania episodes seems to be necessarily associated with adherence to medication and a stabilized routine [17].…”
Section: Discussionmentioning
confidence: 90%
“…Other studies have found similar results in managing mania symptoms using CBT in comparison with TAU in BD [21]. Patients’ cognitive styles may also be involved in the poor adherence to the psychotherapeutic strategies designed for bipolar patients [35,36]. The prophylaxis of mania episodes seems to be necessarily associated with adherence to medication and a stabilized routine [17].…”
Section: Discussionmentioning
confidence: 90%
“…The large sample size and matching of participants by number of previous episodes allowed us to explore if there is an interaction between psychological treatment and number of previous bipolar episodes as some studies have previously shown (22,33), but others have not (34). Number of previous bipolar episodes may be prone to recall bias and are not precise; however, a person with a few episodes can be distinguished readily from someone with 20 or more previous bipolar episodes.…”
Section: Discussionmentioning
confidence: 99%
“…87 A second meta-analysis of ten trials showed an overall RR of 0·74 (0·64-0·85) for mood relapse. 88 …”
Section: Adjunctive Psychotherapy In Long-term Maintenancementioning
confidence: 97%